The manufacture of measures, scales and gauges in the state of Hijaz in the Ottoman period - Qurashi, Manal Muqbil (Journal of Humanities & Social Sciences, 2020)
This research shows the importance of scales, measurements and gauges and their names, in addition to their legal quantities and measures in Hejaz under the Othmani regime, and the introduction of the metric system in the Islamic states. This study presents the difference between scales, measures and their industry for each type, which has different materials, shapes and sizes. This research investigates the important documents that have not been published yet which saved in the Ottoman Archives in Istanbul and reported by the Council of Minister of Ottoman.